If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 2) + 7 = 1x + 6 Reorder the terms: 6(2 + x) + 7 = 1x + 6 (2 * 6 + x * 6) + 7 = 1x + 6 (12 + 6x) + 7 = 1x + 6 Reorder the terms: 12 + 7 + 6x = 1x + 6 Combine like terms: 12 + 7 = 19 19 + 6x = 1x + 6 Reorder the terms: 19 + 6x = 6 + 1x Solving 19 + 6x = 6 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 19 + 6x + -1x = 6 + 1x + -1x Combine like terms: 6x + -1x = 5x 19 + 5x = 6 + 1x + -1x Combine like terms: 1x + -1x = 0 19 + 5x = 6 + 0 19 + 5x = 6 Add '-19' to each side of the equation. 19 + -19 + 5x = 6 + -19 Combine like terms: 19 + -19 = 0 0 + 5x = 6 + -19 5x = 6 + -19 Combine like terms: 6 + -19 = -13 5x = -13 Divide each side by '5'. x = -2.6 Simplifying x = -2.6
| 2xy^2-xy=0 | | 3x+1+3x=67 | | (x-24)+29=360 | | 15+2x=12.5x+2.5 | | 3(y+4)=12 | | 2b-10=5-3b | | 12.5x=10.5 | | -6b=-5b+10 | | 2(y-8)=20 | | 7h=4+6h | | (7(x+5)-18)+(3(x-2)+4)= | | 12.3x-9.2=3x-0.7x | | x+(x*1.08)=188000 | | 7(-3+6x)=-21 | | 2x+3=5x-4+7 | | x^4+1500x^2+1250000=0 | | x*23=33 | | 7x=3x+26 | | 8x-(3x-6)=26 | | 7(2x-1)=11x+5 | | 2a+7=-2-3 | | H=68t-8t | | (9(y+5)-18)+(3(y-3)+5)= | | 5=7-7x | | p^2+4p+4=40 | | 2x-(x+1)= | | (8y-5)6y-7= | | 4(x+5)5=2x-4 | | 6d-11/2=2d-13/2 | | (X+10)2=y+100 | | 24x+19x=180 | | 7/10x=14/5 |